COMPUTERIZATION OF DATA PROCESSING BUSINESS ADS IN THE PT CAMILA INTERNUSA MOVIES - Hotmanatap Hotmanatap; Ir R. A. Gafar. Ir R. A. Gafar. (Jurnal Sistem Informasi, 1996)
Ability of investment firms in computer hardware are often less balanced by theavailability of human resources capable of utilizing the resources of both hardwareand software available software optimally.The same above experienced by PT Camila Internusa Films, where facilities ownedby the company has unused maximally, in the sense applied by the use of the systemwas inefficient. So that if any information is required it must be re-find and mergemultiple data sources manually to the required information is available or can be saidbriefly computers just serve as a type. Then the writer can create a new system thathas more processing speed when compared with the old system and save the datastorage media.